Priorities of consumer behavior based on factor analysis (Journal of Economic Research & Business Administration, 2022)
In the article, the authors substantiate the relevance of studying consumer behavior. The purpose ofthe study is to identify the possibility of using analytical tools to identify the main factors, which influencingconsumer behavior and being a priority to make a purchase decision. The survey method of primaryresearch was chosen among 408 respondents to study this problem. This method was found on the basisof a sample survey called “snowball” method. The method of factorial estimation was used for data analysis.All data were analyzed in IBM SPSS 22 software. The authors describe in details the methodology ofthis study, with the provision of statistical analysis results. The method of factor analysis made it possibleto identify five main factors influencing consumer behavior when they buy car batteries: “basic characteristicsof batteries”, “marketing communications”, “sources of information”, “motivation” and “socialfactors”. The data obtained in the course of the survey allowed us to conclude that consumer behavior inthe car battery market is determined by a combination of various variables within factors. The receivedresults also made it possible to draw a conclusion about the completeness of the identified factors ofconsumer behavior and the need for further research in the context of studying the declared problem.Key words: consumer behavior, factor analysis, purchase decision-making, car batteries.